Development and Bayesian validation of a competitive inhibition ELISA for detection of antibodies against Brucella abortus in cattle - Novoa, María Belén; Aguirre, Nerina; Valentini, Beatriz Susana; Signorini Porchiett, Marcelo Lisandro; Aznar, Maria Natalia; Vanzini, Victor Rene; Torioni, Susana Marta (Elsevier, 2025)
Bovine brucellosis is a zoonotic disease caused by Brucella abortus, responsible for abortions in cows. It is endemic in low- and middle-income countries, where the brucellosis control and eradication programs are based on compulsory vaccination, detection of infected cattle through serologic assays, and culling of infected animals at slaughterhouses. The development of high sensitivity and specificity, and low-cost serologic assays guarantee their implementation in countries where the disease is endemic. The aim of the present study was to develop and validate a competitive inhibition enzyme-linked immune assay (ciELISA) to detect anti-B. abortus antibodies in sera from cattle. The developed ciELISA was validated using 2833 serum samples from dairy and beef cattle. From these, 1515 sera were from uninfected cows that belonged to free of brucellosis herds and 1318 were from infected cows that belonged positive to brucellosis herds. Sera were analyzed with the developed ciELISA, the buffer plate antigen (BPA) test, and the complement fixation test (CFT). The brucellosis status of the herds was officially established according to the country legislation and consistent for at least 5 years and was defined for each cow using the CFT as gold standard. The cutoff for the ciELISA was calculated using a ROC curve and its sensitivity and specificity were analyzed using the Bayesian Latent Class Model (BLCM) approach. The agreement among tests was calculated using the kappa (κ) value. In addition, 15 calves were vaccinated with 3 × 1010 viable cells of B. abortus Strain 19 vaccine, and the dynamics of antibodies were measured by CFT, buffered plate antigen (BPA) test, and the developed ciELISA. The obtained cutoff for ciELISA was ≥ 47 percentage of inhibition (% I), at the BLCM approach the sensitivity was 99.01 % (95 % CI: 97.55–100) and the specificity 98.74 % (95 % CI: 97.68–99.8). The κ between the ciELISA and BPA was κ = 0.88 and between the ciELISA and CFT κ = 0.95. Antibodies against B. abortus were detected in all the vaccinated calves 7 days after vaccination (AV) by the three assays, at day 135 AV all the calves were negative to CFT (15/15), 93.3 % (14/15) to ciELISA and 73.3 % (11/15) to BPA, and at day 190 AV all the calves were negative to the three assays. The developed ciELISA showed a very good performance, could detect the majority of vaccinated animals as negative after 135 days and could be used for the detection of anti-B. abortus antibodies in serum samples for the brucellosis control and eradication program.